Stress among employees in Johor Corporation (JCORP) / Nur Syazwana Abdul Rasid - Abdul Rasid, Nur Syazwana (Faculty of Business and Management, 2018)
In this competitive era, many organization wants to be better without realizing the burden to employees in order to complete their task. Due to that, employee stress can become a problems that can occur to employees in many organization regardless of what industry the employees are involved. Factors of employee stress can be different due to how the organizations handle or managed their employees well. This paper focuses on employee stress and also suggests four variables which are work life balance, workload, role conflict and interpersonal relationship. Work life balance is to ensure whether the employees get to maintain their personal and working life. Workload is refers to whether employee is having too much work or task to do. Role conflict also to determine whether there is one or more conflict of roles in the organization as well as good relationship with managers through interpersonal relationship. What seems importance is to investigate this four factors do influences employee stress or not. Hence, around 186 sample of questionnaire were distributed to employees in Johor Corporation. Total of 170 employee responded and filled the questionnaire, with a response rate of 91.4%. Besides that, results reveal that workload and role conflict is significant. Meanwhile, the work life balance and interpersonal relationship variables reported are not significant.